IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN AGAMA ISLAM - Riyad, Muhamad; Rois, Ajun (Prodi PAI IAILM Suryalaya, 2019)
This study is about the implementation of school-based management and the quality of education with a sample of 30 obtained by the results of the r count value of 0.48 after consultation with the interpretation table